Hubungan Antara Pola Makan Dengan Kejadian Gastritis di Pondok Pesantren AL-qur'an Safinatunnaja Kalibeber Wonosobo - Lu’lu’ul Maknun; Romdiyah Romdiyah; Fifi Alviana (Midwifery Care Journal, 2024)
Gastritis or commonly known as "ulcer" or heartburn is inflammation of the stomach wall, especially the mucous membrane of the stomach. Gastritis is often caused by an incorrect diet. Irregular eating patterns, the stomach becomes sensitive when stomach acid increases. Excessive production of HCI (stomach acid) can cause friction on the walls of the stomach and small intestine, resulting in pain called gastric ulcers. The friction will be worse if the stomach is empty due to irregular eating which will ultimately result in inflammation in the stomach. The main aim of this study is to determine the relationship between the eating patterns of female students and the incidence of gastritis at the Safinatunnaja Islamic boarding school. The approach used in this research is quantitative with a cross-sectional approach. The population in this study were all female students at the Safinatunnaja Islamic boarding school. The sampling technique used a purposive sampling technique of 92 respondents. The time for conducting the research was 24 September – 7 October 2023. The analysis carried out was the chi-square test. The results of the research showed that 58 respondents (63.0%) had unhealthy eating patterns and gastritis compared to 9 respondents (9.8%) with healthy eating patterns. Chi-square test analysis produces a p-value of 0.002 (with α0.05)